Integrating servant leadership theory into the da’wah and leadership curriculum: bridging Islamic principles and contemporary challenge - Illahibaccus Sona, Shaima Banu; Abdullah, Mohammad Ridhuan (2025)
This paper explored the integration of Servant Leadership Theory (SLT) into the Da’wah and Leadership curriculum to address challenges in Islamic leadership amid globalization and societal complexity. Traditional Islamic education often lacks practical leadership training, leaving leaders unprepared for diverse, real-world contexts. SLT, rooted in service, humility, and ethical stewardship, aligns with Islamic values and emphasizes skills like empathy, empowerment, and community building. A qualitative analysis highlights gaps in current curricula, such as fostering interfaith dialogue, engaging diverse audiences, and utilizing digital tools. The study recommends incorporating mentoring, reflective practices, and scenario-based learning while expanding service activities to include social justice and environmental initiatives. This approach equips students with technical skills and reinforces Islamic principles of justice, inclusivity, and ethical leadership, ensuring Da’wah remains relevant and impactful in the 21st century. The proposed model bridges the gap between tradition and modernity, providing a framework for innovation in Islamic studies.